Factors Stimulating Entrepreneurial Success Supported by the Sfax-Innovation 2 Business Incubator - Souissi, Mourad (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
The Tunisian economy is facing major structural challenges, particularly in the labor market, where there is a persistent mismatch between training and job market needs, as well as high unemployment, especially among young people. According to data from the national agency for employment and self-employment in 2023, the youth unemployment rate in Tunisia was close to 23.7% in the second quarter of 2023, one of the highest in the world (National Institute of Statistics, 2024). To meet these challenges, Tunisia has implemented a number of institutional and governmental initiatives aimed at stimulating investment and promoting employment, notably by supporting entrepreneurship among young graduates. These programs include the Youth Employment Promotion Fund (FOPRODI), the